Pengaruh Kualitas Pelayanan Penerbitan Dokumen Perjalanan Republik Indonesia Terhadap Kepuasan Masyarakat Pada Kantor Imigrasi Kelas I Tpi Cilacap - Sutan Ardiansyah; Agung Sulistyo Purnomo; Arief Febrianto (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research aims to determine whether or not there is an influence and to find out how much influence the quality of administrative services for the issuance of the Republic of Indonesia Travel Documents on Public Satisfaction at the Class I Immigration Office of TPI Cilacap. This study uses quantitative methods. The sample used is the applicant for Travel Documents of the Republic of Indonesia at the Immigration Office Class I TPI Cilacap a total of 95 people using a questionnaire. The results of the study explain that there is a significant and positive influence between service quality and community satisfaction. This is indicated by the results of simple regression analysis with a significance obtained of 0.000 <0.05 and a regression coefficient of X, namely the quality of service of 0.441. The magnitude of the influence of service quality on community satisfaction can be seen from the coefficient of determination of 67.5%. So that the quality of service can affect community satisfaction by 67.5% and the remaining 32.5% by other factors. For the future the Class I Immigration Office of TPI Cilacap must always improve the quality of service consistently because if the quality of service is good it will give satisfaction to the community. It is expected that the quality of service at the Class I Immigration Office of TPI Cilacap will be better so that organizational goals can be achieved optimally.